2000
DOI: 10.1038/75718
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activation of AMPA receptors inhibits GABA release from cerebellar interneurons

Abstract: A single neurotransmitter elicits diverse physiological responses through activation of multiple receptor subtypes and/or heterosynaptic interactions involving distinct synaptic targets. We found that a typical excitatory transmitter released from the climbing fiber (CF) in the cerebellar cortex not only excited Purkinje cells directly but also presynaptically inhibited GABAergic transmission from interneurons converging on the same Purkinje cells. Both homosynaptic and heterosynaptic actions of the CF transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 37 publications
6
126
1
Order By: Relevance
“…Together with the present results, these findings suggest activating mGluR2/3 receptors could attenuate hypoglutamatergia by increasing the number of active NMDA-R, possibly via the NMDA-R regulating SRC kinase (Trepanier et al, 2013). mGluR2/3 activation has also been shown to increase non-NMDA glutamate receptor levels (Wang et al, 2013), which could contribute to the restoration of GABAA-R binding levels through reduced GABA release (Drew and Vaughan, 2004;Satake et al, 2000). Finally, Gorrie and colleagues have reported that more than 6 h are required for the synthesis of GABAA-R and its integration into the cell membrane (Gorrie et al, 1997), with GABAA-receptors more likely being recycled back into the membrane than replaced with new receptors (Thomas et al, 2005).…”
Section: The Mglur2/3 Agonist Ly379268 Restores Nmda-r and Gabaa-r Exsupporting
confidence: 53%
“…Together with the present results, these findings suggest activating mGluR2/3 receptors could attenuate hypoglutamatergia by increasing the number of active NMDA-R, possibly via the NMDA-R regulating SRC kinase (Trepanier et al, 2013). mGluR2/3 activation has also been shown to increase non-NMDA glutamate receptor levels (Wang et al, 2013), which could contribute to the restoration of GABAA-R binding levels through reduced GABA release (Drew and Vaughan, 2004;Satake et al, 2000). Finally, Gorrie and colleagues have reported that more than 6 h are required for the synthesis of GABAA-R and its integration into the cell membrane (Gorrie et al, 1997), with GABAA-receptors more likely being recycled back into the membrane than replaced with new receptors (Thomas et al, 2005).…”
Section: The Mglur2/3 Agonist Ly379268 Restores Nmda-r and Gabaa-r Exsupporting
confidence: 53%
“…GluR4 immunogold particles are observed in presynaptic structures at the hair cell ribbon synapse (43) and at the end bulb of Held synapse in the anteroventral cochlear nucleus of auditory brainstem (44). At cerebellar inhibitory synapses (8,45) and spinal cord excitatory synapses (7), presynapticAMPARsinhibittransmitterrelease.Thus,theAMPARmediated presynaptic inhibition may be widespread among central synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at the moment little is known on the relation between synaptically induced calcium transients and DSI/DSE in Purkinje cells. Paradoxically, the only report concerning the effects of high-frequency, glutamatergic fiber stimulation on GABAergic transmission has shown an inhibition after climbing fiber activation which is not dependent on CB1Rs, but rather on presynaptic ionotropic glutamate receptors (Satake et al, 2000).…”
Section: Functional Implications Of Dsi In the Cerebellummentioning
confidence: 99%